The naked gun trilogy [videorecording (DVD)] - Zucker, David, 1947-; Zucker, David, 1947-; Segal, Peter, 1962-; Zucker, Jerry; Proft, Pat, 1947-; LoCash, Robert; Nielsen, Leslie, 1926-2010; Presley, Priscilla Beaulieu; Kennedy, George, 1925-2016; Simpson, O. J., 1947-; Montalbán, Ricardo; Ward, Fred, 1942-2022 (Paramount, 2011)
The 3 Naked gun films all in one package.